The Atraḫasis Epic and Its Place in Babylonian Literature - Miliard, Alan Ralph (1966)
Thesis submitted for the Degree of Master of Philosophy. University of London, May 1966. Supervisor: D. J. Wiseman. 298 p.; Einteilung: I. Discovery and Content of the Epic; II. Text in Transliteration and Translation; III. Notes on the Text; IV. Characteristics of the Old Babylonian Texts; V. Atraḫasis and the Babylonian Creation Stories; VI. Atraḫasis and Other Babylonian Flood Stories; VII. The Atraḫasis Epic and Early History; VIII. The Atraḫasis Epic in Babylonia and Beyond. Appendix: Text of Tablet II, tentatively reconstructed.